Observaciones acerca del Primado en la Iglesia a partir de la Carta de Clemente I y otros escritos de la primera centuria cristiana - Pardo Fariña, Felipe (Veritas, 2010)
Beginning with a review of some New Testament Bible texts and continuing with an incursion in the Letter of St. Clement to the Corinthians, the author strives to present testimony about the authority of St. Peter and his successors. This study is carried considered the historical horizon in which treaties are inscribed passages, allowing you to discover the teaching and problem underlying the beginning of Christianity concerning the nature and mission of the Primate.